The relationship between ethnic-racial socialization and adolescent substance use: An examination of social learning as a causal mechanism. Issue 1 (2nd January 2016) - Grindal, Matthew; Nieri, Tanya
ABSTRACT: The presence of parental socialization messages relevant to a child's race/ethnicity—ethnic-racial socialization (ERS)—have been found to be an important predictor of developmental outcomes. However, scholars have recently called for greater theoretical clarification, citing the need for better understanding of how the effects of ethnic-racial socialization messages differ by dimension and what causal mechanisms underlie this relationship. Using survey data from 269 Southern California high school students, this study tested a theoretical model examining how 3 dimensions of ERS differentially relate to adolescent substance use, and how much these links are mediated by peer substance use social learning (Akers, 2009 ). Using structural equation modeling, we cross-sectionally and longitudinally tested the pathways between ERS and peer substance use social learning and between peer social learning and substance use. We found that 2 of the 3 dimensions of ERS were related to substance use. Cultural socialization was associated with lower substance use, and promotion of mistrust was associated with greater substance use. Both effects were indirect and mediated by peer substance use social learning. These results were replicated in a separate analysis of the largest ethnic subsample (Latinos). Ethnic-racial socialization messages that stress pride in one's ethnic group and the development of one's ethnic identity (cultural socialization) may be a protective factor against future substance use by inhibiting the association with substance-using peers, whereas messages that stress distrust of other ethnic groups (promotion of mistrust) may be a risk factor against future substance use by promoting the association with substance-using peers.